Stan populacji łosia na Ukrainie - Khoyetskyy, Pavlo (Leśne Prace Badawcze, 2011)
The population dynamics of elk (Alces alces) in Ukraine in the period between 1962 and 2009 was analyzed. Three complete and one incomplete cycles of elk population size were identified. The duration of these cycles was 13–15 years and the mean amplitude of fluctuations was about 6.2 thousand individuals. A maximum population size of about 18 thousand individuals was recorded in 1973, although the actual size is thought to be about 5 thousand individuals more than this. The increase in population size never exceeded 30% of the total population, with the mean increase being 9.4±1.5%. The harvest did not exceed 15% of the population, and was on the average 4.8±0.6%. Commercial harvesting and poaching of elks has led to imbalances in the age and sex structure of the population.